Head impacts during sparring: differences and similarities between mouthguard, skin, and headgear sensors - Le Flao, E.; Siegmund, G. P.; Lenetsky, S.; Borotkanics, R. (ISBS Proceedings Archive (Michigan), 2022)
The timely identification of concussions is essential to ensuring athlete safety. In contact sports, many devices are available to measure head impacts, but concerns remain regarding their ability to accurately estimate the number and magnitude of those impacts. This study measured head impacts during boxing sparring simultaneously with three sensors - a mouthguard, a skin patch and a headgear patch - and video analysis. The objective was to assess and compare the number, quality, and magnitude of impact events across sensor types. All sensors had issues related to decoupling from the skull, although the mouthguard appeared to generate better estimates than the patches of the number of impacts and impact-induced head kinematics.